Grupos funcionales alimentarios de macroinvertebrados acuáticos en el río Gaira, Colombia - Javier Rodríguez-Barrios; Rodulfo Ospina-Tórres; Rodrigo Turizo-Correa (Revista de Biología Tropical, 2011)
Para Colombia, la información sobre grupos funcionales alimentarios de macroinvertebrados acuáticos es muy escasa. Por lo tanto, en este estudio se determinó la riqueza, abundancia y biomasa de los GFAs de estos organismos a escala de río, tramo y unidades funcionales, con el objeto de evaluar su variación espacio-temporal. Se seleccionaron tres tramos de 200m. En total se reportan 109 táxones, con una abundancia de 11 167 individuos que aportaron una biomasa de 107.11g. La densidad de los macroinvertebrados se vio favorecida con el incremento en la altura, la biomasa presentó un patrón inverso pues fue mayor hacia el tramo bajo y la diversidad de táxones fue mayor en el tramo medio del río (H’=3.16). Los valores de biomasa de estos organismos fueron mayores en hojarasca seguida de gravas-arenas, epiliton y sedimento. El tramo bajo fue dominado por Macrobrachium con el 73%, seguido de Leptonema con el 15 % en el tramo alto y Anacroneuria con el 6.56 %, en el tramo medio del río. Entre eventos de lluvia y sequía, la biomasa aportada por los grupos funcionales alimentarios fue mayor en lluvia, pero la abundancia fue muy superior durante eventos de sequía. Functional feeding groups of macroinvertebrates in Gaira river, Colombia. Tropical rivers are frequently described on their biodiversity but few studies have considered the ecological value of this richness in their food webs. We determined the trophic structure of aquatic macroinvertebrate communities (expressed in the richness and abundance of taxa and biomass proportions of different functional feeding groups) at the level of the river, stretch and microhabitats (functional units - UFs). We evaluated the spatial and temporal variation of these descriptors during wet and dry events, and selected three sites associated with different altitudinal belts. We reported 109 taxa, with 11 167 individuals who contributed 107.11g of biomass. Density of macroinvertebrates was favored with increasing height, and biomass showed the opposite pattern (K-W=10.1, d.f.=1, p<0.05), due to the addition of large crustaceans (Macrobrachium), and the taxa diversity was higher in the middle stretch of the river (H’=3.16). The Gaira stream runs through a mid-sized river basin, for this reason we found mainly bedrock (epilithon=50.5%), gravel and sand (43.7%). The functional unit with more habitat and food resources that contains a higher abundance of leaf litter macroinvertebrates was foliage followed by epilithon, fine sediment and gravel-sand (K-W=25.3, d.f.=3, p<0.05). The biomass values of these organisms were higher in leaves followed by gravel-sands, epilithon and sediment (K-W=15.3, d.f.=3, p<0.05). Autochthonous biomass input by different functional feeding groups can be considered very low, but they define the functionality of the stream, being represented almost exclusively by shredders (Macrobrachium, 73%), present only in the lower reaches, followed by shredder Leptonema with 15%, located mostly in the upper reaches and predatory stoneflies of the genus Anacroneuria to 6.56%, which dominated in the middle stretch of stream. Excluding Macrobrachium from the analysis, there was dominance of Anacroneuria in the lower reaches. Between rainfall and drought events, biomass of functional feeding groups was higher in rain (W=10.1, d.f.=1, p<0.05), favoring the growth of decapods, but the abundance was much higher during drought events. Rev. Biol. Trop. 59 (4): 1537-1552. Epub 2011 December 01.